Risk for eating disorders modulates interpretation bias in a semantic priming task. (June 2017) - Misener, Kaylee; Libben, Maya
Highlights: Proposed a semantic interpretation bias in non-clinical eating disordered samples. Assessed interpretation bias for food and body shape words. Tested 118 females using a semantic priming paradigm. Elevated scores on the BSQ-34, EAT-26 and EDE-Q 6.0 were associated a semantic interpretation bias. Abstract: The current study used a semantic priming paradigm to investigate the presence of implicit interpretation biases for food and body shape words among 118 undergraduate females. Reaction times (RTs) were recorded while participants made lexical decisions (i.e., word vs. non-word judgments) to lexical targets that were preceded by negatively valenced eating disorder related (e.g., fat-PIZZA), eating disorder unrelated (e.g., party-PIZZA), or semantically unrelated (e.g., umbrella-PIZZA) prime words. Self-reported eating disorder traits were assessed using the Body Shape Questionnaire (BSQ-34), the Eating Attitudes Test (EAT-26), and the Eating Disorder Examination (EDE-Q 6.0). Results suggested that biased RT priming effects for eating disorder related word pairs were strongly associated with measures of body dissatisfaction and ED symptomology. Specifically, scales targeting eating disordered cognitions (the BSQ-34 and the Shape/Weight Concern subscales of the EDE-Q 6.0) demonstrated the strongest association with implicit interpretation biases as assessed by performance on the semantic priming task.